Gambaran Entrepreneurial Self Efficacy Di Era Digital (Studi Fenomenologis Pada Owner Sayunara) - Fitri, Riska Sri Hayani; Putra, Yanladila Yeltas (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research aims to describe the picture of entrepreneurial self-efficacy in the digital era for Sayunara owners. The research is qualitative research with a phenomenological approach. Data resulting from research findings were analyzed and validated with the provisions stated by Miles and Huberman. Data collection on research findings was carried out by in-depth interviews with the owner of Sayunara. In this research, three themes were found with eleven sub themes related to entrepreneurial self-efficacy. The first category consists of sources of entrepreneurial self-efficacy behavior covering the concepts of social modeling, experience, emotional conditions and relationships. The second category is the application of entrepreneurial self-efficacy behavior which covers the concepts of risk taking, innovation, work hard behavior, regularity in business. Meanwhile, the third category is business carried out with the concept of business background, business challenges and business principles.